ESG Risk Disclosure and the Risk of Green Washing - Chitra S de Silva Lokuwaduge; Keshara M. De Silva (Australasian Accounting, Business and Finance Journal, 2022)
There have been growing calls from capital market participants, regulators and other stakeholders around the globe for transparent measurement and disclosure of information about financially material environmental, social and governance (ESG) Risks. Diverse approaches to and objectives of sustainability standards and frameworks pose the threat of increasing greenwashing, a term which encompasses a wide range of actions which exaggerate and misrepresent ‘green’ credentials . Traditional financial reporting is regulated, mandatory, and required to meet the qualitative characteristics; relevance, reliability, comparability, materiality and understand ability. However, ESG reporting is problematic due to reporting quality which does not meet the above criteria. Apart from that ESG reporting is not regulated in most part of the world. A global framework is needed to prevent fragmentation, provide greater comparability, transparency and reduce the complexity of ESG disclosure which could mitigate the risk of greenwashing as the ESG is increasingly considered to be a fundamental part of effective and sustainable business performance.
Keywords: ESG; Sustainability reporting; ESG disclosure; Green washing; ESG strategy